Effects of biochar and modified biochar on Chromium contaminated soil properties - Siddika, Asha; Rabbani, AFM Masum; Parveen, Zakia; Hossain, Md. Faruque (AIUB Journal of Science and Engineering (AJSE), 2023)
In recent years, increasingly more soils are getting contaminated with organic and inorganic toxins globally due to waste emissions. Among inorganic pollutants, heavy metals like carcinogenic chromium (Cr) are alarming to our environment, even though its environmental management is also ignored. As a result, Cr accumulates in plant tissues at toxic concentrations and ends up in the food chain. Therefore, pot experiments were conducted to investigate the effects of biochar and modified biochar application on the properties of Cr polluted soils and interaction of Cr with other soil nutrients. Two different biochar viz. rice stubble and saw dust were slowly pyrolyzed (450 ± 50ºC) and modified with 1M KOH. All biochars were applied at a rate of 20 t ha-1 on soils artificially polluted with Cr at the levels of 0, 100, 200 and 300 µg g-1 . The biochars and modified biochars had significant effects (P<0.05) on available K, P, CEC, EC, and N of incubated soils. Therefore, it has convincing evidence that application of biochar and modified biochar is very imperative to improve soil health, ameliorate Cr polluted soils, reduce the amount of carbon produced due to biomass burning and thereby enhances plant growth.